Implementasi Six Sigma dalam Peningkatan Kualitas Proses Produksi LED TV di PT Sharp Electronics Indonesia - Phengky Pangestu; Fakhrina Fahma (Performa: Media Ilmiah Teknik Industri, 2018)
Competition in the electronic industry in Indonesia is very tight, which encourages industries to compete with each other. PT Sharp Electronics Indonesia as one of the companies that produce television, especially Light Emitting Diode (LED) TV, often has problems related to quality, which are still many defects that occur in the production process. Based on the calculation of the DPMO (defects per million opportunities) average value and the sigma average value in January 2019, it was 672.67 and 4.71 respectively. The process capability index (Cpk) of production is 1.07724. The purpose of this study is to reduce the number of defects in PT Sharp Electronics Indonesia television factories using Six Sigma through the Define, Measure, Analyze, Improve, and Control (DMAIC) stages. This quality improvement is simulated with a Monte Carlo simulation which is divided into 3 scenario success solutions (reduced number of no raster, no picture and no power defects). The Cpk value in the simulation results increases to 1.1; 1.11; and 1.12.